In ovo Feeding of Butyric Acid Replacing Antibiotics Function to Increase Poultry Productivity - Rantan Krisnan; Yuli Retnani; Budi Tangendjaja; Rita Mutia; Anuraga Jayanegara (Indonesian Center for Animal Research and Development, 2019)
Antibiotics have an important role in increasing livestock productivity. The ban on the use of these products encourages efforts to find substitute products. Butyric acid is one of the organic acids and considered to be potential to replace the role of antibiotics. In principle, both antibiotics and butyric acids can create livestock conditions physiologically and metabolically well to achieve good productivity. Several mechanisms of butyric acid in increasing livestock productivity can provide explanation for the positive effects of this material. Characteristics of butyric acids such as corrosive, volatile and have unpleasant odor encourage the need for an appropriate application technology. In ovo feeding technology can be the right solution to eliminate the constraints of using butyric acid. This technology has also been widely studied and proven to increase livestock productivity through improved hatching parameters, performance of livestock, improvement of organs/digestive tract (intestine), repair of bones, muscles and meat, and enhancement of immunity.